Desenvolvimento de um flotador por ar dissolvido em coluna de estágios para tratamento de águas oleosas. - Santos, Leonardo Bandeira dos (2018)
A dissolved air flotation column - FAD, commonly uses principles of operation based on the operation of a gas-liquid fluidized bed. In the present research, a column scale FAD column was developed, consisting of stages, similar to a distillation column, for the treatment of oily waters. The prototype bench was made of transparent acrylic with polyvinyl chloride - PVC pipes and structural aluminum support structure. The flow of the liquid effluent is passed through a centrifugal pump, adapted to induce and saturate the air microbubble liquid. The oil-rich foam is drained from the top of the stage and the residual oily water flows by gravity to the lower stage, where the remainder of the separation between the foam and the liquid occurs. This equipment showed some additional advantages over conventional FAD columns, such as: less horizontal physical space; compressor removal and saturation vessel; variable number of stages according to the degree of purity of treated water, lower energy consumption, operation independent of atmospheric conditions; use of a simple hydraulic seal for level control; analogy of operation with reactors of perfect mixture in series, facilitating the obtaining of correlations of scale-up. Operational conditions diagrams were obtained for the system that presented an oil removal efficiency of 89%, reducing 150 mg.L-1 of the tested effluent to 16.5 mg.L-1, according to the requirements of the Council National Environment Organization (CONAMA).